Controlling Aqueous Self‐Assembly Mechanisms by Hydrophobic Interactions. Issue 43 (8th September 2014) - Rudolph, Tobias; Kumar Allampally, Naveen; Fernández, Gustavo; Schacher, Felix H.
Abstract: We report an innovative template‐assisted synthetic protocol for the selective functionalization of terminal triple bonds in oligophenyleneethynylenes (OPE) by pre‐organization in aqueous solution. By this approach, three new OPE‐based bolaamphiphiles substituted with hydrophilic poly(2‐ethyl‐2‐oxazoline) (PEtOx) chains of different length have been synthesized. The chain length was observed to strongly influence the aqueous supramolecular polymerization: bolaamphiphiles with longer hydrophilic chains aggregate into spherical nanoparticles in a stepwise fashion, whereas 2D anisotropic platelets are formed cooperatively if shorter PEtOx chains are used. Our results demonstrate that hydrophobic interactions can be strong enough to trigger cooperative effects in aqueous self‐assembly processes. Abstract : Cooperative chemistry! Three oligophenyleneethynylene‐based bolaamphiphiles of various length have been synthesized by a pioneering template‐ assisted copper‐catalyzed azide–alkyne cycloaddition (CuAAC) click chemistry protocol. Bolaamphiphiles featuring longer PEtOx chains self‐assemble into spherical nanoparticles in water, whereas anisotropic superstructures are formed as a result of cooperative hydrophobic interactions (see scheme).